Microorganisms in Air-Conditioning and Ventilation Installations in Hospitals - Charkowska, Anna; Tabernacka, Agnieszka (Instal, 2024)
The article refers of the problem of the occurrence of microorganisms in air-conditioning and ventilation systems serving health care facilities and their impact on the condition of the air supplied to the premises. The available results of studies of the state of microbiological cleanliness of ventilation and air conditioning systems in hospitals are discussed, including occurrence of particular groups and species of microorganisms, seasonal variation, and the equipment and places most at risk of microbial colonization. The need has been identified to define the types of microorganisms whose presence in ventilation systems should be controlled and to determine the permissible abundances of these microorganisms in ventilation air and in the deposits inside air-conditioning and ventilation systems.
Keywords: microorganisms; hospitals; ventilation ducts; HVAC unit; seasonal variability